Kinematic instability in the joints of flatfoot subjects during walking: A biplanar fluoroscopic study - Phan, Cong Bo; Lee, Kyoung Min; Kwon, Soon Sun; Koo, Seungbum (Journal of Biomechanics, 2021)
Abnormal foot kinematics is observed in flatfoot subjects with postural foot deformity. We aimed to investigate joint instability in flatfoot subjects by analyzing the abnormal rotational position and speed of their joints while walking. Five flatfoot subjects participated in our study. Three-dimensional motions of the tibia, talus, calcaneus, navicular, and cuboid were obtained during walking using the biplanar fluoroscopic motion analyses. An anatomical coordinate system was established for each bone. The rotations and ranges of motion (ROMs) of the joints from heel-strike to toe-off were quantified. The relative movements on the articular surfaces were quantified by surface relative velocity vector analysis. The data from flat foot subjects were compared with the data from normal foot subjects in previous studies. The average relative speed on the articular surface of the tibiotalar, subtalar, and calcaneocuboid joints for the flatfoot subjects was significantly higher (p < 0.05) than that for the normal foot subjects. The flatfoot subjects exhibited increased movements toward plantar flexion in the tibiotalar joint, and eversion and external rotations in the talonavicular joint during the stance phase, compared to the normal subjects (p < 0.01). Furthermore, the flatfoot subjects had a significantly larger ROM along with the inversion/eversion rotations (5.6 ± 1.8° vs. 10.7 ± 4.0°) and internal/external rotations (7.1 ± 1.5° vs. 10.5 ± 3.5°) in the tibiotalar joint. The flatfoot subjects demonstrated abnormal kinematics and larger joint movements in multiple joints during the mid-stance and terminal stance phases of walking. This demonstrates their high instability levels.
Keywords: Articular surfaces; Bi-planar fluoroscopic system; Biplanar; Flatfoot; Foot joint kinematic; Midtarsal joint; Range-of-motion; Subtalar joints; Tibiotalar joint; Walking; Ankle Joint; Biomechanical Phenomena; Flatfoot; Humans; Range of Motion, Articular; Talus; Walking; Bi-planar fluoroscopic system; Flatfoot; Foot joint kinematics; Midtarsal joint; Subtalar joint; Tibiotalar joint; Walking